Longitudinal Microstructural Changes in Traumatic Brain Injury in Rats: A Diffusional Kurtosis Imaging, Histology, and Behavior Study - Wang, M.-L. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: Traumatic brain injury is a major public health problem worldwide. Accurately evaluating the brain microstructural changes in traumatic brain injury is crucial for the treatment and prognosis assessment. This study aimed to assess the longitudinal brain microstructural changes in traumatic brain injury in the rat using diffusional kurtosis imaging. MATERIALS AND METHODS: Diffusional kurtosis imaging was performed in a group of 5 rats at preinjury and 3, 14, and 28 days after traumatic brain injury. The diffusional kurtosis imaging parameters were measured in the bilateral cortex, hippocampus, and corpus callosum. Another 4 groups of 5 rats were used in brain immunohistochemistry analysis of neuron (neuron-specific nuclear protein [NeuN]), astroglia (glial fibrillary acidic protein [GFAP]), microglia (ionized calcium binding adaptor molecule 1 [Iba-1]), and myelin (myelin basic protein [MBP]) in the same area as the diffusional kurtosis imaging parameter measurements. Furthermore, 2 groups of 6 rats underwent a Morris water maze test at 28 days after traumatic brain injury. The diffusional kurtosis imaging parameters, immunohistochemistry results, and Morris water maze test results were compared longitudinally or between traumatic brain injury and control groups. RESULTS: Compared with baseline, traumatic brain injury in the rat showed higher mean kurtosis and mean diffusivity values in the ipsilateral perilesional cortex and hippocampus and lower fractional anisotropy values in the corpus callosum (P < .05). The traumatic brain injury group showed higher staining of GFAP and Iba-1 and lower immunohistochemistry staining of NeuN and MBP in all ipsilateral ROIs (P < .05). There was no significant difference in the contralateral ROIs in diffusional kurtosis imaging parameters or immunohistochemistry results. The Morris water maze test revealed lower platform crossing times in the probe test (P < .05). CONCLUSIONS: Our study indicated that there were longitudinal changes in diffusional kurtosis imaging parameters, accompanied by multiple pathologic changes at different time points following traumatic brain injury, and that mean kurtosis is more sensitive to detect microstructural changes, especially in gray matter, than mean diffusivity and fractional anisotropy.